Willingness and hesitancy of parents to vaccinate against COVID-19 their children ages 6 months to 4 years with frail conditions in Italy - Miraglia del Giudice, Grazia; Della Polla, Giorgia; Postiglione, Mario; Angelillo, Italo Francesco (Frontiers in Public Health, 2023)
Background In Italy, on December 2022, COVID-19 vaccination was recommended for children aged 6 months-4 years with frail conditions and for those healthy. The purposes of the survey were to understand parental willingness and hesitancy toward COVID-19 vaccination of children with frail conditions in Italy and related influencing factors. Methods A cross-sectional survey was performed among 445 parents with a child aged 6 months-4 years with frail conditions who attended a teaching hospital and a public hospital randomly selected in the city of Naples, Italy. Results Almost one third (29.9%) were willing to vaccinate their frail children against COVID-19, whereas 21.3% were uncertain, and 48.8% did not intend to vaccinate. Parents with a higher level of perception that the vaccine is useful and safe and those who had received information by pediatrician were more likely to be willing to vaccinate their child. The mean Parent Attitudes About Childhood Vaccines (PACV-5) score was 3.4, with 13.5% of parents high-hesitant for the COVID-19 vaccination for their child. Parents with a higher COVID-19 vaccine-related safety concerns, those who have delayed at least one shot of a recommended vaccine for their child, and those who did not have received at least three doses of the vaccine against SARS-CoV-2 were more likely to be high-hesitant. Conclusion The survey findings have important implications for designing interventions to increase willingness and to reduce hesitancy for COVID-19 vaccine among parents of frail children aged 6 months-4 years in Italy.